PKM Pendampingan Guru Madrasah Ibtidaiyah Nurul Mun’im dalam Mengoptimalkan Peran Wali Murid dalam Pembelajaran Daring - Muhammad Ainul Yaqin; Abd Halim; Ahmad Zainullah; Zainul Badri; Abdullah Abdullah (GUYUB: Journal of Community Engagement, 2021)
During this pandemic, to break the chain of the spread of COVID-19, the government swiftly issued a policy to change face-to-face education to distance or online education. So it is possible that some obstacles arise in this teaching and learning process. Even though there are obstacles, it is hoped that the guardians of students optimally guide their children so that they are always enthusiastic about learning through online education. Helping teachers in the process of maximizing the position of guardians during this pandemic is the decision of the head of the madrasa to always carry out education so that this teaching and learning goal is always achieved.In this online learning, it is hoped that the guardians of students will play an optimal role in being able to directly guide their children to stay focused and enthusiastic in learning. One of the problems that arise in these online learning activities is the limited access to the internet or also the media that supports online learning using either a cellphone or laptop and other media. However, it is hoped that students will remain enthusiastic about learning and the role of parents is very important in optimizing this online learning activity.